DENTAL PRACTICE AND EDUCATION DURING THE COVID-19 PANDEMIC: CURRENT CHALLENGES AND SOLUTIONS - Pyndus Тетяна; Bondarenko Валентина; Stetsenko Дмитро; Pyndus Володимир; Dorosh Ірина (Actual Problems of Medicine and Pharmacy, 2022)
Since the World Health Organization (WHO) declared the coronavirus outbreak (COVID-19) a pandemic in March 2020, the world has begun an unprecedented change in the organization of all areas of human life. Such conditions have become a difficult challenge for dental care and education institutions. This review collects materials from text databases PubMed, Scopus, Web of Science, Open Gray, Google Scholar, on the features of dental care and dental education in the context of the COVID-19 pandemic, as well as the coexistence of diseases of the oral cavity and COVID-19.